Judge's Considerations in Granting the Request for Marriage Dispensation - Sintiarawati Abdullah (Universitas Negeri Gorontalo, 2023)
Implementation of Law No. 16 of 2019 concerning marriage on dispensation of marriage, a factor that was considered by the judges of the Limboto religious court in granting the request for dispensation of marriage after the enactment of UU No. 16 of 2019 concerning marriage.The Limboto Religious Court implements and implements Law Number 16 of 2019 concerning Marriage. The law regulates the minimum age for marriage as stated in article 7 paragraph (1), namely marriage is only permitted if a man and a woman have reached the age of 19. Then in Article 7 paragraph (2) In the event of a deviation from the age requirement as referred to in paragraph (1), the parents of the man and/or the parents of the woman can request dispensation from the Court with very urgent reasons accompanied by sufficient supporting evidence. . Article 7 paragraph (3) states that the granting of dispensation by the Court as referred to in paragraph (2) must listen to the opinions of both bride and groom who will enter into a marriage